1970
DOI: 10.3329/fmcj.v6i1.7405
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sociodemographic and Clinical Factors Associated with Hospitalized Stroke Patients of Bangladesh

Abstract: A hospital based cross sectional study was carried out to analyze prevalence of risk factors for stroke in hospitalized patient in a medical college hospital. 100 patients were chosen using purposive sampling technique. Highest incidence of stroke was between the 6th and 7th decade. Patients came from both urban (54%) and rural (46%) areas and most of them belong to the low-income group (47%). In occupational category; service holder (28%) and retired person (21%) were the highest groups. Most of the study sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
24
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 12 publications
14
24
3
Order By: Relevance
“…The Copenhagen stroke study has shown that in 1135 acute stroke patients, 233 (20%) were suffering from diabetes mellitus 8 which is similar to our result. This results also correlates with the study of AM Hossain et al 7 (21%) and with MR Siddique et al 9 (11%). This result also correlates with the study in India 10 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The Copenhagen stroke study has shown that in 1135 acute stroke patients, 233 (20%) were suffering from diabetes mellitus 8 which is similar to our result. This results also correlates with the study of AM Hossain et al 7 (21%) and with MR Siddique et al 9 (11%). This result also correlates with the study in India 10 .…”
Section: Discussionsupporting
confidence: 82%
“…Our study had showed that 6% had heart disease (4% valvular heart disease and 2% ischaemic heart disease). This was much less than that of AM Hossain study 7 and of Hayee study 15 .…”
Section: Discussioncontrasting
confidence: 40%
“…Average monthly income of the majority group was less than TK 5000 in a study. 6 The present study showed that the study population resided almost equally in rural and urban areas. Majority of the stroke patients of the present study were found to be married.…”
Section: Discussionsupporting
confidence: 47%
“…The burden of the disease is increasing both in our country and globally 2,3 . In Bangladesh, there is no adequate data on incidence and mortality from stroke 4 . The American Health Association estimates that 780 000 strokes occur each year; 600,000 of these are new strokes, and 180,000are recurrent strokes 5 .…”
Section: Introductionmentioning
confidence: 99%